Pengukuran Indeks Keberlanjutan Industri Gula - Hartrisari Hardjomidjojo; Sapta Raharja; Muti'atul Chosyi'ah (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
Sugar is one of the potential plantation commodities from the agricultural sector in Indonesia. The huge population of Indonesia is causing high sugar consumption quantity every year. This condition is not supported by the national sugar high productivity, resulting in import of refined sugar. The purpose of this study is to measure the sugar industries’ sustainability indexes to increase the improvement strategies priority. This study uses a Multidimensional Scaling (MDS) method with eight dimensions that consist of thirty-four attributes. The analysis is performed for two years, from 2012-2014 in the sugar industry as a case study in this study. Successive performance is considered in “good” condition, however the material dimension should be the priority concern in future improvement.